2016
DOI: 10.1002/pip.2813
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunction solar cells with 23% efficiency onn-type epitaxial kerfless silicon wafers

Abstract: We present a heterojunction (HJ) solar cell on n-type epitaxially grown kerfless crystalline-silicon with an in-housemeasured conversion efficiency of 23%. The total cell area is 243.4 cm 2 . The cell has a short-circuit current density of 39.6 mA cmÀ2 , an open-circuit voltage of 725 mV, and a fill factor of 0.799. The effect of stacking faults (SFs) is examined by current density (J) mapping measurements as well as by spectral response mapping. The J mapping images show that the localized lower J regions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…2 In recent years, a-Si:H layers also garnered significant attention, thanks to their excellent crystalline silicon (c-Si) surface passivation properties, even when only a few nm thin. [3][4][5][6][7][8] This property is exploited with remarkable success for passivating-contact fabrication in silicon heterojunction (SHJ) solar cells, [9][10][11][12][13][14][15][16][17][18][19][20][21][22] with reported conversion cell efficiencies as high as 26.3%. 23 For any solar cell technology, an important criterion for ultimate device performance is its stability under prolonged light exposure.…”
mentioning
confidence: 99%
“…2 In recent years, a-Si:H layers also garnered significant attention, thanks to their excellent crystalline silicon (c-Si) surface passivation properties, even when only a few nm thin. [3][4][5][6][7][8] This property is exploited with remarkable success for passivating-contact fabrication in silicon heterojunction (SHJ) solar cells, [9][10][11][12][13][14][15][16][17][18][19][20][21][22] with reported conversion cell efficiencies as high as 26.3%. 23 For any solar cell technology, an important criterion for ultimate device performance is its stability under prolonged light exposure.…”
mentioning
confidence: 99%
“…Another reason being the minimal parasitic absorption by the MoO x layer due to its large energy band gap (≈3.2 eV) in comparison to the conventional SHJ with the highly absorbing a‐Si:H(i) layers (≈1.7 eV) . Also, the thicker layers are required for better surface passivation in conventional SHJ, which can affect the electrical properties of the cell by showing non‐ideal electrical behavior apart from the parasitic absorption loss …”
Section: Resultsmentioning
confidence: 99%
“…This 2D majority carrier transport effect leads to less restriction on the conductivity of front TCO layer for the rear emitter SHJ solar cell compared with its front emitter counterpart . Therefore, suppressing the light absorption in the front TCO layer should be more important in improving the efficiency of the rear emitter cell.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, based on the design of the rear emitter cell, Watahiki et al have successfully realized a 23.43% efficient SHJ solar cell by utilizing an n‐type microcrystalline Si layer as the window layer instead of the normally used a‐Si:H(n) layer. Kobayashi et al have reported a rear emitter SHJ solar cell with an efficiency of 23% using an epitaxial kerfless silicon wafer substrate. However, it should be noted that the research work on the rear emitter SHJ solar cell is still limited and there lacks a competitive study for deep understanding of the design principle and process optimization of the rear emitter SHJ solar cell.…”
Section: Introductionmentioning
confidence: 99%